2008
DOI: 10.1203/pdr.0b013e31815ed03e
|View full text |Cite
|
Sign up to set email alerts
|

Fetal Onset of General Movements

Abstract: Perinatal qualitative assessment of general movements (GMs) is a tool to evaluate the integrity of the young nervous system. The aim of this investigation was to study the emergence of GMs. Fetal onset of GMs was studied sonographically in 18 fetuses during the first trimester of uncomplicated in vitro fertilization (IVF) pregnancies in weekly assessments. The earliest motility consisting of small and simple sideways bending (SB) of head and/or rump starts at 7 wk, lasting about 1 s. Between 7 and 8.5 wk, moti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
88
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(93 citation statements)
references
References 16 publications
2
88
0
3
Order By: Relevance
“…In humans, small, slow, cyclic bending of the head and/or trunk are detected with 4D-ultrasonography at 5 weeks post-conception [8]. Waxing and waning general movements can be observed slightly later, at 7 weeks, and persist throughout pregnancy and the first months after term birth [9][10][11]. They consist of complex, variable, flexion-extensions of the whole body and limbs, they are not triggered by external stimuli and lack distinctive sequencing of different body parts.…”
Section: Prenatal Movementsmentioning
confidence: 99%
“…In humans, small, slow, cyclic bending of the head and/or trunk are detected with 4D-ultrasonography at 5 weeks post-conception [8]. Waxing and waning general movements can be observed slightly later, at 7 weeks, and persist throughout pregnancy and the first months after term birth [9][10][11]. They consist of complex, variable, flexion-extensions of the whole body and limbs, they are not triggered by external stimuli and lack distinctive sequencing of different body parts.…”
Section: Prenatal Movementsmentioning
confidence: 99%
“…Qualitative changes in general movements can also be observed. 6 Using fourdimensional (4D) sonography, we have found that from 13 gestational weeks onwards, a goal orientation of hand movements appears and a target point can be recognized for each hand movement. According to the spatial orientation, they classified the hand movements into several subtypes: hand to head, hand to mouth, hand near mouth, hand to face, hand near face, hand to eye and hand to ear.…”
Section: Prenatal Morphological and Functional Development Of The Fetmentioning
confidence: 99%
“…Spontaneous self‐generated movements are seen to occur in utero as early as 7 weeks gestational age (Lüchinger, Hadders‐Algra, van Kan, & de Vries, 2008). At this first stage, movements of the arms are associated with writhing movements of the trunk and whole body (de Vries, Visser, & Prechtl, 1982; Prechtl, 1986).…”
Section: Introductionmentioning
confidence: 99%